2014
DOI: 10.5858/arpa.2013-0335-oa
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy Assessment of Endoscopic Ultrasound-Guided, Fine-Needle Aspirations of Pancreatic Masses for Theranostic Studies: Optimization of Current Practices Is Warranted

Abstract: Changes in practice, such as obtaining dedicated passes for ancillary studies, may not be enough to improve the theranostic utility of endoscopic ultrasound-guided fine-needle aspiration in pancreatic neoplasia. Other methods to improve tumor cell yield, including modified cytologic techniques and new needle designs, need to be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…In particular, tissue samples from PDAC may be hypocellular with small numbers of neoplastic cells outnumbered by non‐neoplastic stroma and inflammatory cells. One study found that only 12.4% of 169 EUS‐FNA cell block specimens obtained from malignant solid pancreatic masses had adequate cellularity for theranostic studies . A retrospective study concurrently assessing percutaneous FNA and core needle biopsies found improved cellularity, higher tumor fractions, and better NGS metrics with FNA‐acquired specimens compared with core samples, suggesting that FNA may be sufficient for NGS .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, tissue samples from PDAC may be hypocellular with small numbers of neoplastic cells outnumbered by non‐neoplastic stroma and inflammatory cells. One study found that only 12.4% of 169 EUS‐FNA cell block specimens obtained from malignant solid pancreatic masses had adequate cellularity for theranostic studies . A retrospective study concurrently assessing percutaneous FNA and core needle biopsies found improved cellularity, higher tumor fractions, and better NGS metrics with FNA‐acquired specimens compared with core samples, suggesting that FNA may be sufficient for NGS .…”
Section: Discussionmentioning
confidence: 99%
“…EUS‐guided tissue sampling has emerged as an invaluable procedure for the evaluation and diagnosis of lesions within the gastrointestinal tract and adjacent organs. EUS‐guided FNA is a widely accepted method of tissue sampling because it is a convenient, safe, minimally invasive procedure that has the ability to provide diagnoses with good sensitivities and specificities . However, the ability to acquire an adequate EUS‐FNA specimen is influenced by numerous factors such as the location of the lesion, the consistency of the lesion, the gauge of the needle used to sample the lesion, the degree of technical difficulty required to obtain the sample, the experience and skill of the endosonographer, and the presence of an onsite cytopathologist .…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability to acquire an adequate EUS‐FNA specimen is influenced by numerous factors such as the location of the lesion, the consistency of the lesion, the gauge of the needle used to sample the lesion, the degree of technical difficulty required to obtain the sample, the experience and skill of the endosonographer, and the presence of an onsite cytopathologist . In addition, there is an increased interest in designing larger needles for EUS‐guided histologic tissue sampling because of the limited cellularity obtained with EUS‐FNA, the need to do more preoperatively for patients requiring neoadjuvant treatment, and the need for tissue fragments to help in the diagnosis of lymphomas, stromal tumors, pancreatitis, and other reactive processes . Early attempts at a biopsy needle included large needle gauges, such as the 19‐gauge Trucut spring‐loaded cutting biopsy needle (Quick‐Core, Cook Medical), which is technically difficult to use and has a higher risk of complications .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations